A tecnologia assistiva para a inclusão de estudantes com deficiência na educação superior: concepção e avaliação de um portal educacional para auxiliar a prática docente. - LOPES, Ana Paula de Sousa (2019)
The inclusive education has been representing a challenge for college education, justifying a strong need for deep studies in this area and for professional improvement in education to effect the inclusion of students with disabilities in college education institutions, in terms of adaptation of materials, methodologies and evaluations. From this context, Assistive Technology resources related to the area of computing facilitate the communication and open new possibilities for people with disabilities. It is essential to prepare the college professors to facilitate the access to the learning process for the included students. In this perspective, this research aimed to design an educational portal about the use of Assistive Technology (TA), oriented to teachers of college education so they can work together with students with disabilities. The research was based on a methodological model known as Development Methodologies, which applies to research in the field of Educational Technology, with a method of quantitative-qualitative approach, whose fundamentals supported the process of validation of the prototype. For the data collection, questionnaires were applied to the usability and content test of the portal composed of a series of multiple choice and also open questions sent to the experts of the area, in addition to an interview addressed to the coordinator of the UFMA Accessibility Center, which were analyzed through statistical analysis and content analysis, discussed from the point of view of the theoretical reference of this research. Therefore, the developed portal was validated by experts from the area who confirmed that the Tecassistiva Portal has technical characteristics that facilitate its use and contribute in the scope of the inclusive educational practice of college professors. It is verified that with this research we can contribute to the academic community interested in the theme and the community in general, giving tools to the professors, in order to prepare them to an inclusive pedagogical practice, to a inclusion in college education. It is also aimed that the portal will be a support to help the teaching practice and a space for reflection regarding the support for students with disabilities.